LOCAL WISDOM-BASED DIGITAL STORYTELLING IN ELEMENTARY SCHOOL LEARNING: A SYSTEMATIC LITERATURE REVIEW OF THE GOOGLE SCHOLAR DATABASE - Utami, Putri; Abdul Wachid Bambang Suharto (Journal of Language and Literature Education, 2026)
This study aims to systematically examine the implementation of local wisdom-based digital storytelling in elementary school learning and its contribution to students’ literacy development. The background of this study is based on the importance of integrating technology and local culture to enhance the quality of contextual and meaningful learning. The method used is a Systematic Literature Review (SLR) by analyzing scientific articles indexed in Google Scholar based on specific inclusion and exclusion criteria. The analysis process is conducted through identification, selection, evaluation, and synthesis of data from various relevant studies. The results indicate that local wisdom-based digital storytelling is effective in improving reading and writing literacy, digital literacy, as well as cultural and civic literacy among students. In addition, this approach is also able to enhance learning motivation, conceptual understanding, and critical thinking skills. Therefore, the integration of digital storytelling and local wisdom becomes an innovative and relevant strategy to support 21st-century learning in elementary schools. Keywords: Digital storytelling, local wisdom, learning